Screening, Identification, and optimization of extracellular lipase production of yeast (Cryptococcus flavescens) isolated from a tree canopy fern in Mount Makiling Forest Reserve, Philippines - Elegado, Francisco B. (Animo Repository, 2019)
Lipases (triacylglycerol acylhydrolases, E.C. 3.1.1.3) are enzymes vastly used in industrial applications. The current study aims to screen lipase-producing yeasts isolated from a tree canopy fern from the Makiling Forest Reserve (MFR), Philippines and to optimize conditions that can maximize the mass production and activity of the enzyme. From the 144 isolates, B1-7 showed the highest lipase activity in both solid (EIA 7.6) and liquid selection media (0.082 U/mL- min). Molecular identification using Internally Transcribed Spacer (ITS) primers and microscopic observation revealed that the isolate was Cryptococcus flavescens, a generally regarded as safe (GRAS) microorganism. Response Surface Method (Box-Behnken Design) showed that the maximum lipase activity (0.66 U/mL-min) and a biomass of 4 g/L were achieved at 5.0 Carbon:Nitrogen ratio, pH 6.0 and 0.5% inducer (Tween 20). Also, C:N-% inducer interaction and inducer concentration significantly affected lipase activity. After a 72h fed-batch fermentation experiment, lipase activity was ten- fold lower than the optimization results and a negative correlation (r=-0.405) between lipase activity and biomass suggested the non-dependence of lipase activity to biomass availability. Lastly, total sugar concentration remained constant implying that the organism used the degradative products of lipase as its carbon source. In conclusion, C. flavescens from MFR can be utilized for mass lipase production, but it was recommended that other parameters be examined and optimized.